Organophosphate Pesticides Use and Contamination in Groundwater of Pakistan: A Review - Sadia, Mamoona; Mohsin, Muhammad; Rehman, Muhammad Sami ur; Iqbal, Zafar; Rehman, Abdur; Naheed, Nargis (The Nucleus, 2023)
Water pollution and contamination is a grave risk to the human as well as environment in Pakistan augmented by the disposal of industrial waste, fertilizers and pesticides into the water sources. The objective of this review paper is to sum-up the use and evaluating the studies of organophosphate pesticides contamination in groundwater of Pakistan. This review paper also pinpoints the detrimental effects of these pesticides on to the human health and environment. It also considers the present state of familiarity to fix the future action plan in research on pesticides in Pakistan. It is manifested that pesticides have a long history of use against insects and other pests. Pesticides are used to enhance agricultural productivity as well as for indoor applications, however, their side effects include damaging the useful insects, wildlife losses, ruins the crops and food chain and health danger to the human and animals etc. It is also evident that in Pakistan, the groundwater is being contaminated at higher levels with the excessive use of pesticides especially organophosphates. It is also noted that a little work has been done on residues analyses of these organophosphates in groundwater of Pakistan especially in Punjab province. Therefore, in order to make sustainable use of pesticides and decrease their harmful impacts, the strong implementation of legislation is required and the utilization of pesticides should be reduced. Furthermore, favoring the biological control and integrated pest management (IPM) should be the main focus of the quarters concerned.